2017
DOI: 10.4269/ajtmh.16-0646
|View full text |Cite
|
Sign up to set email alerts
|

Nonnative Cattle Ownership, Diet, and Child Height-for-Age: Evidence from the 2011 Uganda Demographic and Health Survey

Abstract: Abstract. In underresourced settings where domestic animals and children often cohabitate, there is limited evidence about the net impact of domestic animal ownership on child health. We analyzed the 2011 Uganda Demographic and Health Survey to determine whether household ownership of native cattle, goats, sheep, chickens, pigs, and nonnative cattle was associated with child height-for-age z-scores (HAZ), and to assess the influence of diet on this association in rural and urban environments. Using weighted mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The main nding of association between dairy animal ownership and household milk consumption was corroborated by a large study from India [11], and also smaller studies from Ethiopia (23% increased frequency) [8], Uganda [12,22] and Kenya [23]. This was found to be especially important in areas without access to markets [8], which was not the case in our study area where dairies have been established.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The main nding of association between dairy animal ownership and household milk consumption was corroborated by a large study from India [11], and also smaller studies from Ethiopia (23% increased frequency) [8], Uganda [12,22] and Kenya [23]. This was found to be especially important in areas without access to markets [8], which was not the case in our study area where dairies have been established.…”
Section: Discussionsupporting
confidence: 84%
“…A study from Ethiopia indicated positive impact on reducing stunting [8]. Studies from Uganda found signi cant positive impact [12], no impact [22], or even negative impact of dairy animal ownership on child nutrition, and hence, there must be other contextual factors, such as availability and use of sanitation and intra-household competition for resources. Small ruminants (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…126 articles were excluded based on a review of the title and abstract ( Fig 1 ). Of the 64 reports selected for full-text review, 24 were excluded: 7 studies reported results for one domain but did not include measurements of linear growth [ 71 77 ], 6 studies reported measurements of linear growth but did not report domain measurements [ 78 83 ], and 1 study abstract did not report results for domains or stunting [ 84 ]. Five abstracts [ 85 – 89 ] and five full-text articles [ 90 94 ] included overlapping EED measurements on the same study subjects and were excluded from our review.…”
Section: Resultsmentioning
confidence: 99%
“…Recent observational research on the impact of livestock managed in traditional extensive systems in sub-Saharan Africa on child stunting has yielded mixed findings ( S1 Table , [ 9 20 ]), with the most consistent evidence for a positive effect coming from analyses of the specific impact of dairy cow or goat ownership [ 9 13 ]. However, others have reported no association between livestock ownership and stunting [ 14 16 ], a modest relationship depending on how “livestock ownership” was operationalized [ 17 , 18 ], or even a negative effect in some situations [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%